Enhancing vocabulary with mobile applications and interactive platforms (Texas Journal of Philology, Culture and History, 2024)
The abundance of electronic resources (e-resources) in the digital era has changed the scene of vocabulary acquisition and language instruction. This article investigates the effectiveness of e-resources, specifically mobile applications and interactive platforms, in improving vocabulary abilities in intermediate learners. Also, in this article, the pedagogical consequences of using e-resources in vocabulary education are addressed, and recommendations for both educators and learners are made. These recommendations aim to enhance the teaching and learning experience by integrating effective e-resources into vocabulary instruction. By doing so, educators can better support learners in developing their vocabulary skills in a more engaging and accessible manner.